(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The paper analyses women names in Lvivschyna. The main means of identifying married woman were personal names and andronyms, suffixal derivatives of husband’s names or surnames.